THE MOTIVATION OF MANAGERS AND THEIR INFLUENCE ON EMPLOYEES MOTIVATION - Dragiša Delić (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu, 2011)
The human resourcesmanagement also includes the use of correspondingrules, and in some situations, the respect ofestablished and common procedure. The majorityof these rules apply when the measures andactivities are undertaken in the area of personnelpolicy. One of the basic principles of personnelpolicy is - the right man to be in the right place.This rule applies to managers, no matter in whichmanagement rank they are. One of the importantdeterminants of motivation is not only themotivation of employees, that is subordinates, butalso the motivation of managers, that is superiors.It is obvious that they are employed as well, with allthe responsibilities that await them, with theirhopes for the successful conduct of companies andtheir salaries. Their influence as content managersis essential for the employees in the company. Inthis paper, we are going to explain the motivationof managers, job satisfaction and leadership, andactivities and influence of good managers onmotivation of employees.